Profiles of Tumor-Infiltrating Lymphocytes in a Case of Trichilemmal Carcinoma with Spontaneous Regression - Sadanori Furudate; Taku Fujimura; Akira Tsukada; Yukikazu Numata; Yumi Kambayashi; Setsuya Aiba (Karger Publishers, 2012)
We describe the case of a 69-year-old Japanese patient with spontaneous regression of trichilemmal carcinoma. We investigated the immunohistochemical profiles of tumor-infiltrating lymphocytes, focusing on cytotoxic granules, granulysin-bearing cells and immunosuppressive cells, such as regulatory T cells and tumor-associated macrophages. Our present study describes some of the possible mechanisms of the self-regression of cutaneous malignant tumors and potential therapies for trichilemmal carcinoma by modifying the tumor microenvironment.